Transformasi Pesantren (Studi terhadap Dialektika Kurikulum dan Kelembagaan Pondok Pesantren Rifaiyah Pati) - Mahmud, Amir; AR, Zaini Tamin (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2019)
This study intends to analyze curriculum changes Islamic boarding schools that are now a discourse due to policy dynamics development of the national education curriculum. At the same time, Dynamics of Islamic Boarding Schools in Developing Curriculum, with establish formal educational institutions that absorb substance curriculum needed by the community. The author makes Rifaiyah Pati Islamic boarding school as the object of research considering This pesantren survives with the development of a dialectical curriculum. Using a qualitative approach, the data collected analyzed with an inductive narrative, then presented in a chronological-analytical. The findings of this study are that The development of the Rifaiyah Islamic boarding school has several cases that unique and dynamic, starting from a shift in development orientation curriculum, intellectual traditions, to the opposition that caused by a misunderstanding of the ideological direction Boarding. These specific cases of course affect institutional policies run by Rifaiyah Islamic boarding schools in realizing its vision, mission and goals in the future. From this, The author draws a common thread that the change of Islamic boarding schools often starts from the curriculum, then penetrates to the aspects that other such as institutions